Pergerakan Kamera sebagai Penguat Unsur Dramatik pada Film Pengabdi Setan 2: Communion - Berlian Syabantoro; I Putu Suhada Agung (CandraRupa : Journal of Art, Design, and Media, 2025)
The film Pengabdi Setan 2: Communion has an important aspect in terms of cinematography, more precisely in camera movement, because if cinematographic elements are combined into one in a series of scenes, they can strengthen the visuals, apart from that, the messages and impressions contained in the film can be conveyed to the audience. This research aims to determine the presence of dramatic elements in camera movement. The research method uses descriptive qualitative with observation and literature study data collection techniques The research was conducted by observing scenes in the film that include many camera movements and dramatic elements that emerge from the camera movements. Based on the observation results, 217 camera movements were found, data reduction was carried out to select scenes that contained dramatic elements from camera movements, which contained 18 scenes in the form of dramatic elements of horror, tension (suspense) and surprise. Data analysis was carried out by observing scenes that had undergone a data reduction process that was adjusted to the theoretical basis of camera movements and dramatic elements.. The results of the research show that camera movements in films are able to strengthen dramatic elements with different feelings. The camera movement that is often used in this film is handheld in 11 scenes which can increase the dramatic element with the majority of it being tense (suspense). The movement of a handheld camera moving in a shaky and unstable manner can create a more natural image, so that it can give the impression of tension (suspense) for the audience and strengthen the dramatization of scenes in the film.